A dictionary of the names of the Seal of the Prophets (may God bless him and his family and grant them peace) and some of his attributes - Hassan, Jaafar (Al-Adab Journal, 2024)
In this research, I decided to study the names of the Prophet Muhammad (may God’s prayers and peace be upon him and his family and all his companions) in the light of ancient and modern Arabic dictionaries, in order to clarify their meanings and reveal the reasons behind giving those names to him so we went to adopt the alphabetical system or whatever. It is called the chapters that lexicographers followed in writing their dictionaries for ease of access by the reader. The research came in two parts, the first began with the chapter on the hamza and concluded with the chapter on the ain, while the second began with the chapter on the fa and concluded with the chapter on the ya. One of the most important results that we reached in the guidance of this research is that the names of the Prophet (peace be upon him) often come in the form of an active participle, an exaggerated form, or a similar adjective. This is in terms of Meaning, in addition to that, some of them were named from their many characteristics.